Finnish cleantech SMEs in China: Challenges and solutions - Karjula, Hans (My University, 2013)
The rapid economic growth in China has resulted in environmental challenges ranging from air pollution to water-related issues. Thus supporting clean technology, or cleantech, that encompasses industries that focus on alternative energy, pollution and recycling, power supplies and conservation has become one of the focal points in the Chinese economic policy for the next decade. Simultaneously, the Finnish government has initiated programs to support the internationalisation of domestic cleantech companies in an attempt to spiral the industry into one of the pillars of Finnish economic growth. This study concentrates on the conjunction of these two themes and studies the challenges faced by Finnish cleantech SMEs in the Chinese market. Consequently, the study answers the following sub questions: 1. What human and financial resource-based challenges do Finnish cleantech SMEs face in the Chinese market and what are their solutions? 2. What knowledge-based challenges do Finnish cleantech SMEs face in the Chinese market and how can these difficulties be resolved? 3. What network-based challenges do Finnish cleantech SMEs face in the Chinese market, how do they relate to the resource- and knowledge-based challenges, and how can these difficulties be resolved? This qualitative study is conducted by analysing four semi structured interviews collected from four Finnish SMEs that operate in China. The findings of the study indicate that in human resources the most important challenges are related to the hiring and retaining of employees. In contrast to extant academic literature results distinguish salary and social status as the main solutions to this challenge. Regarding financial resources it is discovered that cleantech companies enjoy a benign business environment in China and benefit from the Chinese government’s support for cleantech industry. Challenges related to knowledge resources can be grouped into categories with the most interesting knowledge flows being the stream of local market knowledge into to the foreign parent company and the outward flow of manufacturing and business practice information into the target venture. The challenge related to the first flow is gathering relevant information and the main solutions are clustering at the foreign location and hiring knowledge prior to internationalisation. Regarding the second flow the main challenge is related to intellectual property rights and the most interesting solution is the purposeful transformation of explicit knowledge into tacit knowledge. Finally, it is discovered that networks, called guanxi in China, greatly affect the business processes. Within the guanxi system there is the concept of face which was found to affect employee propensity to stay as well as, as a novel academic result, employees’ knowledge sharing intention.